Effect of Si/Al Ratio on Competitive CO₂/H2O Adsorption in FAU Zeolite for Humid Flue Gas Capture: A Computational Study - Mustafa Jassim Radhi (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Carbon capture from humid flue gas is problematic. Many microporous adsorbents are poisoned by water vapor. This research aims to study the effect of the Si/Al ratio on the competitive adsorption of CO₂ and H₂O in FAU-type zeolites, as well as evaluate their performance in capturing humid flue gases. Grand Canonical Monte Carlo (GCMC) simulations were performed to study the competitive adsorption of equimolar CO₂/H₂O mixtures at 298 K in two FAU zeolites: Zeolite 13X (Na₇₇, Si/Al ≈ 1.5) and Zeolite Y (Na₄₉, Si/Al≈2.92). The results showed that Zeolite 13X shows higher adsorption of CO₂ under low pressures, with the phenomenon of the roll-over occurring in the case of high pressure because of competitive adsorption with H₂O. In turn, the adsorption of CO₂ for Zeolite Y remained stable over the entire pressure range and exhibited lower H₂O uptake. Isosteric heats of CO₂ adsorption on the zeolites are 15.71 kcal/mol for Zeolite 13X and 13.23 kcal/mol for Zeolite Y. The energy of CO₂ binding in the presence of H₂O decreased by 1.14 kcal/mol for Zeolite 13X and for 2.03 kcal/mol for Zeolite Y. These findings indicate that high-silica FAU zeolites, such as Zeolite Y, are efficient CO₂ adsorbents. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).